Insertion sequence content reflects genome plasticity in strains of the root nodule actinobacterium Frankia - Bickhart, Derek M; Gogarten, Johann P; Lapierre, Pascal; Tisa, Louis S; Normand, Philippe; Benson, David R (BMC genomics, 2009)
Background Genome analysis of three Frankia sp. strains has revealed a high number of transposable elements in two of the strains. Twelve out of the 20 major families of bacterial Insertion Sequence (IS) elements are represented in the 148 annotated transposases of Frankia strain HFPCcI3 (CcI3) comprising 3% of its total coding sequences (CDS). EAN1pec (EAN) has 183 transposase ORFs from 13 IS families comprising 2.2% of its CDS. Strain ACN14a (ACN) differs significantly from the other strains with only 33 transposase ORFs (0.5% of the total CDS) from 9 IS families. Results Insertion sequences in the Frankia genomes were analyzed using BLAST searches, PHYML phylogenies and the IRF (Inverted Repeat Finder) algorithms. To identify putative or decaying IS elements, a PSI-TBLASTN search was performed on all three genomes, identifying 36%, 39% and 12% additional putative transposase ORFs than originally annotated in strains CcI3, EAN and ACN, respectively. The distribution of transposase ORFs in each strain was then analysed using a sliding window, revealing significant clustering of elements in regions of the EAN and CcI3 genomes. Lastly the three genomes were aligned with the MAUVE multiple genome alignment tool, revealing several Large Chromosome Rearrangement (LCR) events; many of which correlate to transposase clusters. Conclusion Analysis of transposase ORFs in Frankia sp. revealed low inter-strain diversity of transposases, suggesting that the majority of transposase proliferation occurred without recent horizontal transfer of novel mobile elements from outside the genus. Exceptions to this include representatives from the IS3 family in strain EAN and seven IS4 transposases in all three strains that have a lower G+C content, suggesting recent horizontal transfer. The clustering of transposase ORFs near LCRs revealed a tendency for IS elements to be associated with regions of chromosome instability in the three strains. The results of this study suggest that IS elements may help drive chromosome differences in different Frankia sp. strains as they have adapted to a variety of hosts and environments.